Implementation and coordination of Agricultural Research and training(ICART)in the SADIC Region (Gaborone: SADIC Secretariate, 2008)
The analysis included the following SADIC Countries:Angola,Democratic Republic of Congo Mozambiaque,SouthAfrica,Botswana,Tanzania,Swaziland,Namibia,Madagascar,Malawi,Mauritius
Keywords: Agricultural Research and Training---SADIC Region